FOCUS STUDY ON HALAL TOURISM PROMOTION - Fadli Agus Triansyah (JASIE, 2023)
Halal tourism is a type of tourism that follows the rules and principles of Islamic sharia. This includes services and facilities designed to meet the needs of Muslim travelers, such as Halal food, access to mosques or places of worship, separate accommodation for men and women, and recommended modest dress. This study utilised a systematic review on halal tourism promotion scopus database from 2021-2023. In this research, the keyword used is "Halal tourism promotion" in the Scopus database. After conducting the screening, the researchers found 6 articles that met the predetermined criteria. The focus of the entire research is Group model building, System dynamics, Causal loop diagram, Alternative tourism, Mass tourism, CrescentRating, Non-mass tourism, Sweden; secularism; adaptations; values; gender equity; Muslim friendly tourism, strategic model, tourism development, Destination image, Travel motivation, Religiosity, Islamic attributes of destination, Visiting intention, Destination competitiveness, Intention to visit, Perceived behavioral control, Perceived value, and Trust. The promotion of halal tourism is very important in meeting the increasing needs of Muslim tourists, boosting the local economy, building a positive image of a tourist destination, and increasing intercultural understanding and harmony.